Computing, analytics and networks : first International Conference, ICAN 2017, Chandigarh, India, October 27-28, 2017, Revised selected papers /: first International Conference, ICAN 2017, Chandigarh, India, October 27-28, 2017, Revised selected papers. (2018) - Unknown
No abstract available